Cross-Dialectal Influences on English Language Learning among Bangladeshi EFL Learners - Kaniz Fatema (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2024)
The phrase "Cross Linguistics," also known as "Translanguaging" in a broader sense, serves as the basis for this research’s core point of discussion. It is needless to describe the importance of the English language in Bangladesh, where it has gained the status of a second official language. The paper intends to unfold every possible kind of influence on Bangladeshi English Language Learners having different dialects while learning it as a Foreign Language. Researchers have surveyed around 45 tertiary-level language learners from some prominent universities in Bangladesh. Both qualitative and quantitative data collection methods have been followed, along with tools like interviews and surveys, on the selected samples for this research. The outcome of this research endeavor is expected to provide us with a clear focus on both the positive and negative effects of using cross-dialectal forms by English Language Learners.